GMAT Question of the Day - Daily to your Mailbox; hard ones only

 It is currently 14 Oct 2019, 08:41

### GMAT Club Daily Prep

#### Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track
Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

# If the graph of y = x^2 + ax + b passes through the points

 new topic post reply Question banks Downloads My Bookmarks Reviews Important topics
Author Message
TAGS:

### Hide Tags

GMATH Teacher
Status: GMATH founder
Joined: 12 Oct 2010
Posts: 935
Re: If the graph of y = x^2 + ax + b passes through the points  [#permalink]

### Show Tags

08 Jan 2019, 05:00
1
aeros232 wrote:
If the graph of y = x^2 + ax + b passes through the points (m, 0) and (n, 0), where m < n, what is the value of n – m ?

(1) 4b = a^2 – 4

(2) b = 0

$$? = n - m$$

$$n > m\,\,\,{\rm{are}}\,\,{\rm{the}}\,\,{\rm{roots}}\,\,{\rm{of}}\,\,{\rm{the}}\,\,{\rm{equation}}\,\,\,{x^2} + ax + b = 0\,\,\,\,\left( * \right)\,\,\,\,\,\mathop \Rightarrow \limits^{{\rm{sum/product}}} \,\,\,\,\,\,\,\,\left\{ \matrix{ \,m + n = - a \hfill \cr \,mn = b \hfill \cr} \right.$$

$$\left( 1 \right)\,\,4b = {a^2} - 4\,\,\,\,\, \Rightarrow \,\,\,\,\,\Delta = {a^2} - 4b = 4$$

$$\left( * \right)\,\,\,\,\, \Rightarrow \,\,\,\,\,\,\left\{ \matrix{ \,n = {{ - a + \sqrt \Delta } \over 2} = - {a \over 2} + 1 \hfill \cr \,m = {{ - a - \sqrt \Delta } \over 2} = - {a \over 2} - 1 \hfill \cr} \right.\,\,\,\,\,\,\,\,\, \Rightarrow \,\,\,\,\,? = n - m = 2$$

$$\left( 2 \right)\,\,b = 0\,\,\,\, \Rightarrow \,\,\,\,mn = 0\,\,\,\,\,$$

$$\left\{ \matrix{ \,{\rm{Take}}\,\,\left( {n,m} \right) = \left( {1,0} \right)\,\,\,\, \Rightarrow \,\,\,\,a = - 1\,\,\,\,\, \Rightarrow \,\,\,\,{x^2} - x = 0\,\,\,\,\left( {{\rm{viable}}} \right)\,\,\,\,\, \Rightarrow \,\,\,\,\,\,? = 1 \hfill \cr \,{\rm{Take}}\,\,\left( {n,m} \right) = \left( {2,0} \right)\,\,\,\, \Rightarrow \,\,\,\,a = - 2\,\,\,\,\, \Rightarrow \,\,\,\,{x^2} - 2x = 0\,\,\,\,\left( {{\rm{viable}}} \right)\,\,\,\,\, \Rightarrow \,\,\,\,\,\,? = 2\,\, \hfill \cr} \right.$$

This solution follows the notations and rationale taught in the GMATH method.

Regards,
Fabio.
_________________
Fabio Skilnik :: GMATH method creator (Math for the GMAT)
Our high-level "quant" preparation starts here: https://gmath.net
CEO
Joined: 12 Sep 2015
Posts: 3995
Location: Canada
If the graph of y = x^2 + ax + b passes through the points  [#permalink]

### Show Tags

Updated on: 15 Jan 2019, 06:57
Top Contributor
aeros232 wrote:
If the graph of y = x² + ax + b passes through the points (m, 0) and (n, 0), where m < n, what is the value of n – m ?

(1) 4b = a² – 4

(2) b = 0

Given: The graph of y = x² + ax + b passes through the points (m, 0) and (n, 0)

Target question: What is the value of n – m ?
This is a good candidate for rephrasing the target question.

The quadratic formula tells us that, if ax² + bx + c = 0, then $$x=\frac{-b\pm\sqrt{b^2-4ac}}{2a}$$

We're told that (m, 0) and (n, 0) are on the graph of y = x² + ax + b.
In other words, m and n are the two x-values that result in y = 0
In other words, m and n are the two solutions to the equation x² + ax + b = 0

When we apply the quadratic formula to the equation x² + ax + b = 0, we get two solutions:
SOLUTION 1
$$x=\frac{-a+\sqrt{a^2-4(1)(b)}}{2(1)}$$
$$=\frac{-a+\sqrt{a^2-4b}}{2}$$

SOLUTION 2
$$x=\frac{-a-\sqrt{a^2-4(1)(b)}}{2(1)}$$
$$=\frac{-a-\sqrt{a^2-4b}}{2}$$

So, one of the two solutions (above) is equal to m and the other is equal to n
We're told that m < n
So, it must be the case that n = solution 1, and m = solution 2 (since one solution has + $$\sqrt{{a^2 - 4(1)(b)}}$$ and the other solution has - $$\sqrt{{a^2 - 4(1)(b)}}$$

That is, $$m=\frac{-a-\sqrt{a^2-4b}}{2}$$
and $$n=\frac{-a+\sqrt{a^2-4b}}{2}$$

So, $$n - m = \frac{-a+\sqrt{a^2-4b}}{2} - \frac{-a-\sqrt{a^2-4b}}{2}$$
$$= \frac{2\sqrt{a^2-4b}}{2}$$

$$= \sqrt{a^2-4b}$$

REPHRASED target question: What is the value of √(a² - 4b)?

Now that we've REPHRASED the target question, it will be easy to analyze the statements

Aside: I've posted a video (below) with tips on rephrasing the target question

Statement 1: 4b = a² – 4
Take √(a² - 4b) and replace 4b with a² – 4
We get: √[a² - (a² – 4 )]
Simplify to get: √(4)
Evaluate to get: 2
So, the answer to the REPHRASED target question is √(a² - 4b) = 2
Since we can answer the REPHRASED target question with certainty, statement 1 is SUFFICIENT

Statement 2: b = 0
Take √(a² - 4b) and replace b with 0
We get: √[a² - 4(0)]
Simplify to get: √(a²)
Since we don't know the value of a, there's no way to determine the value of √(a²)
Since we cannot answer the REPHRASED target question with certainty, statement 2 is NOT SUFFICIENT

Answer: A

Cheers,
Brent

RELATED VIDEO FROM OUR COURSE

_________________
Test confidently with gmatprepnow.com

Originally posted by GMATPrepNow on 14 Jan 2019, 09:16.
Last edited by GMATPrepNow on 15 Jan 2019, 06:57, edited 1 time in total.
SVP
Joined: 26 Mar 2013
Posts: 2341
Re: If the graph of y = x^2 + ax + b passes through the points  [#permalink]

### Show Tags

14 Jan 2019, 23:11
1
GMATPrepNow wrote:
aeros232 wrote:
If the graph of y = x² + ax + b passes through the points (m, 0) and (n, 0), where m < n, what is the value of n – m ?

(1) 4b = a² – 4

(2) b = 0

Given: The graph of y = x² + ax + b passes through the points (m, 0) and (n, 0)

Target question: What is the value of n – m ?
This is a good candidate for rephrasing the target question.

The quadratic formula tells us that, if ax² + bx + c = 0, then $$x=\frac{-b\pm\sqrt{b^2-4ac}}{2a}$$

We're told that (m, 0) and (n, 0) are on the graph of y = x² + ax + b.
In other words, m and n are the two x-values that result in y = 0
In other words, m and n are the two solutions to the equation x² + ax + b = 0

When we apply the quadratic formula to the equation x² + ax + b = 0, we get two solutions:
SOLUTION 1
$$x=\frac{-a+\sqrt{a^2-4(1)(b)}}{2(1)}$$
$$=\frac{-a+\sqrt{a^2-4b}}{2}$$

SOLUTION 2
$$x=\frac{-a-\sqrt{a^2-4(1)(b)}}{2(1)}$$
$$=\frac{-a-\sqrt{a^2-4b}}{2}$$

So, one of the two solutions (above) is equal to m and the other is equal to n
We're told that m < n
So, it must be the case that m = solution 1, and n = solution 2 (since one solution has + $$\sqrt{{a^2 - 4(1)(b)}}$$ and the other solution has - $$\sqrt{{a^2 - 4(1)(b)}}$$

That is, $$m=\frac{-a+\sqrt{a^2-4b}}{2}$$
and $$n=\frac{-a-\sqrt{a^2-4b}}{2}$$

So, $$m - n = \frac{-a+\sqrt{a^2-4b}}{2} - \frac{-a-\sqrt{a^2-4b}}{2}$$
$$= \frac{2\sqrt{a^2-4b}}{2}$$

$$= \sqrt{a^2-4b}$$

REPHRASED target question: What is the value of √(a² - 4b)?

Now that we've REPHRASED the target question, it will be easy to analyze the statements

Aside: I've posted a video (below) with tips on rephrasing the target question

Statement 1: 4b = a² – 4
Take √(a² - 4b) and replace 4b with a² – 4
We get: √[a² - (a² – 4 )]
Simplify to get: √(4)]
Evaluate to get: 2]
So, the answer to the REPHRASED target question is √(a² - 4b) = 2
Since we can answer the REPHRASED target question with certainty, statement 1 is SUFFICIENT

Statement 2: b = 0
Take √(a² - 4b) and replace b with 0
We get: √[a² - 4(0)]
Simplify to get: √(a²)
Since we don't know the value of a, there's no way to determine the value of √(a²)
Since we cannot answer the REPHRASED target question with certainty, statement 2 is NOT SUFFICIENT

Answer: A

Cheers,
Brent

RELATED VIDEO FROM OUR COURSE

Dear GMATPrepNow Brent,

Although you reached solution, you swapped m & n.

The question states that n>m.....So n must have the term with positive (solution 1) and m with negative (solution 2) to match.

Please see the highlight, it must be n-m = 2 to match the question stem.
CEO
Joined: 12 Sep 2015
Posts: 3995
Location: Canada
Re: If the graph of y = x^2 + ax + b passes through the points  [#permalink]

### Show Tags

15 Jan 2019, 06:58
Top Contributor
Mo2men wrote:
Dear GMATPrepNow Brent,

Although you reached solution, you swapped m & n.

The question states that n>m.....So n must have the term with positive (solution 1) and m with negative (solution 2) to match.

Please see the highlight, it must be n-m = 2 to match the question stem.

Good catch!!
I've edited my response accordingly.

Cheers and thanks,
Brent
_________________
Test confidently with gmatprepnow.com
Re: If the graph of y = x^2 + ax + b passes through the points   [#permalink] 15 Jan 2019, 06:58

Go to page   Previous    1   2   3   [ 44 posts ]

Display posts from previous: Sort by

# If the graph of y = x^2 + ax + b passes through the points

 new topic post reply Question banks Downloads My Bookmarks Reviews Important topics

 Powered by phpBB © phpBB Group | Emoji artwork provided by EmojiOne